Improved sorbent for the removal of hydrocarbons spilled in water - Díaz, Miguel Angel Díaz; Frómeta, Amado Enrique Navarro; Muñoz, Carlos Lázaro Sosa (Frontiers in Sustainability, 2022)
Oil contamination of ecologically sensitive aquifer systems is a major global environmental problem. Depending on their availability, there is a trend to seek sorbent materials based on natural fibers, for their high adsorption capacity and biodegradability. The objective of this work was to obtain a sorbent material, by carbonizing sugarcane bagasse chemically modified to clean the water contaminated by oil. Tests were carried out to determine the sorption capacity of the carbonized material as a type II sorbent according to ASTM method F 726-17. The optimal particle size for which the sorption capacity was greater, was above 2.0 mm. The sorbent obtained was tested on water contaminated with crude oil, and a comparative evaluation was made between this material and a commercially existing one. As a result of the experiments, very similar values were obtained between the properties of both sorbent materials. Thus, it is concluded that the carbonized bagasse material can be used as hydrocarbon sorbent material.